Pancreatic Tuberculosis: A Case Report - Sarkar, H; Hassan, M; Ali, S; Laila, RN (TAJ: Journal of Teachers Association, 2009)
The pancreas is rarely affected by Mycobacterium tuberculosis infections, probably because of the presence of pancreatic enzymes and only few cases are reported. The differential diagnosis with pancreatic carcinoma represents a challenge because of clinical and radiological similarities. We report a case of 30 year-old women presented with pain and lump in epigastric region with constitutional symptoms - weight loss, nausea and occasional vomiting. Preoperative diagnosis of pancreatic tuberculosis requires a high index of suspicion and usually its diagnosis is established after surgical treatment. The diagnosis of this reported case was confirmed by histopathological analysis following laparotomy. The response of the disease to anti tubercular drugs was good. TAJ 2009; 22(1): 264-268